The aspects of reaction time in elite sprinters of different age and gender - Lingyte, E.; Stanislovaitis, A.; Kudirkaite, J.; Skurvydas, A. (Education. Physical training. Sport, 2004)
Sprinter`s reaction times are now frequently displayed during high-level competitions. Among track events including indoor competition, from 60 m to 400 m, reaction time may be considered as an important element in the results (both performance and place). The purpose of this study was to examine the peculiarities of reaction time (RT) of different age, gender and sport skill at the short distance runners. Subjects were the world-class sprinters (male and female) who took part in the final sprint races of the World Athletics Championships and of the Junior World championships (age to 20 years old) (n = 332). Also we examined the Lithuanian elite class sprinters (n = 15). The obtained results showed that gender has not made significant differences for the sprinter`s reaction time, but the age determines it. World-class sprinter`s RT are significantly better than those of junior sprinter`s at 100 m race. Statistically significant differences were found among distances. 100 m sprinter`s (male and female) reaction time is better than 400 m runner`s. According to our research we can draw the conclusion that 100 m runners may avoid too many anaerobic-lactic physical loads.